EARLY–MIDDLE ORDOVICIAN GRAPTOLITES FROM THE EASTERN PUNA, ARGENTINA: QUANTITATIVE PALEOBIOGEOGRAPHIC ANALYSIS BASED ON A SYSTEMATIC REVISION (Ameghiniana, 2020)
The updated taxonomic revision of the Early–Middle Ordovician graptolites from the eastern Argentine Puna allows describing Sigmagraptus praecursor, Baltograptus extremus, B. geometricus, B. vacillans, Cymatograptus protobalticus, Expansograptus constrictus, E. pusillus, E. similis, and Corymbograptus v-fractus tullbergi for the first time in this region. The analyzed material was collected from the volcano-sedimentary deposits assigned to the Cochinoca-Escaya Magmatic-Sedimentary Complex and exposed at the Muñayoc and Santa Rosa sections, Jujuy Province. This taxonomic analysis confirms the occurrence of 23 taxa in the studied region, from which S. praecursor, B. extremus, and E. pusillus were not previously documented in South America. Additionally, it contributes to the clarification of the faunal graptolite affinities earlier postulated for Northwestern Argentina. Quantitative paleobiogeographic analyses of clusters and principal coordinates were carried out, including the described species and previous certain graptolite assignations for the Puna region, to quantify its faunal affinities with Baltoscandia, Great Britain, North America, and Southwestern China. Finally, our results are discussed and compared with those formerly obtained in paleobiogeographic analyses based on different fossil groups from Northwestern Argentina.